Does terrorism reduce life satisfaction?. Issue 13 (29th July 2017) - Farzanegan, Mohammad Reza; Krieger, Tim; Meierrieks, Daniel
ABSTRACT: We study the effect of terrorism on life satisfaction for a sample of 81 countries over the 1994–2009 period. We find that terrorism is robustly associated with less life satisfaction. This effect, however, translates into only modest social costs.